Modern Recommendations for Treating Anaphylactic Shock in Children - R. F. Tepaev; L. R. Selimzyanova; L. S. Namazova-Baranova; E. A. Vishnyova (Union of pediatricians of Russia, 2015)
Anaphylaxis is an immediate hypersensitivity reaction. It is characterized by the rapid development of life-threatening conditions caused by circulatory and respiratory disorders, in some cases with lesions of the skin and mucous membranes, and is associated with serious complications, including death. A steady increase in the incidence of various forms of anaphylaxis has been noted in recent decades. Experience shows that many specialists tend to make mistakes after facing severe forms of anaphylaxis (and especially the most severe its manifestation - anaphylactic shock),. These mistakes can not only affect the patient's quality of life, but also in some cases lead to serious and even fatal consequences. The article deals with the epidemiology and pathogenesis, describes the clinical picture of anaphylaxis/anaphylactic shock, and gives an algorithm for the treatment of the disease. The algorithm is based on European Academy of Allergy and Clinical Immunology recommendations published in 2014.